Impact of Counseling on Cancer Patient’s Depression Level - Himalay Choudhary; Lalita Rathore; Lokesh Bhardwaj; Yashawant Ramawat; Jim Samuel; Yogeshwar Kumar Mutha; Shatrughan Pareek (International Journal of Oncological Nursing and Practices, 2023)
Introduction: When given the dreaded and possibly fatal cancer diagnosis, patients go through a great deal of pain. Depression is one of the psychiatric problems that can arise after a cancer diagnosis. The purpose of the current research is to evaluate how well counseling therapy can lower depression levels in cancer patients. Methodology: Geetanjali Hospital in Udaipur provided the data for this study, which utilized a single-group, quasi-experimental analysis employing a pre-test, one-group post-test design. A practical sampling method was employed to select a total of 60 samples from the hospital's IPD (In-Patient Department) units. Result: As per findings, majority of patients (68.33%) had moderate, while 31.67% have mild depression. After the intervention, most of the patients (88.33%) were normal followed by 8.33% had mild depression and 03.33% had moderate depression. Moreover, stages of cancer and therapy method were having significant association with depression score. Conclusion: The current research found that counseling was highly effective in lowering stress levels in cancer patients. It is necessary to create a strategy for providing emotional support to all cancer patients.
Keywords: Counselling therapy; Depression; cancer diagnosis; cancer patient; emotional support